COMPARISON OF MEANS TO INCREASE THE BRAND'S OWN AUDIENCE ON SOCIAL NETWORKS - Костинець, Юлія; Колесник, Богдан (Journal of Strategic Economic Research, 2022)
Internet technologies have always been considered perspective by marketers due to its scale, which is the number of people that can be reached and its possibilities for statistical measurement. Nevertheless, with an increase in the number of users, the Internet has turned into a congested public space in which it is no less difficult to stand out than at a traditional bazaar. From the very beginning of the internet technologies development, search engines have played a leading role; because of them, traditional banners and classifieds were replaced by contextual advertising. Social networks have involved even further, by inventing more accurate targeting methods, which is an advertising mechanism that allows to select from the entire audience only a segment that meets a specified criteria (target audience) and show ads to them. Greater accuracy is possible since social media can only be used by an authorized user. In addition, the portfolio of collected data has been significantly expanded. All of this has formed the so-called Web 2.0 and modern digital marketing tools. The struggle of companies for consumer attention on the internet remains an important topic; owing to social networks, it becomes possible to retain a certain fraction of a brand’s target audience. Hence, there is a need to explore strategies for increasing brand’s engaged audience on social networks. The subject of the study is the comparison of internet marketing tools effectiveness and traditional marketing communications, as well as analysis of brand management methods on the example of the large business; formulating a hypothesis regarding the possible evolution of a given efficiency model. In this work the dialectical method of scientific knowledge, the method of analysis and synthesis, the comparative method, and the method of generalizing data are used. The paper defines the place and role of a brand management strategy regarding a size increase of a company’s own audience on social networks. The characteristics of internet advertising and traditional means of marketing communications, as well as special intermediaries on social networks in Ukraine have been compiled. The world trends of some online advertising aspects have been analyzed. Suggestions of social media business strategies have been outlined. The results of the study lead to the following conclusions: a set of strategies for effectively expanding companies’ owned media, which can be applied in Ukraine and worldwide have been identified; values of performance indicators and audit methods have been suggested.